Development of a Minimum Competency Assessment Instrument (AKM) for Students' Scientific Literacy on Hooke's Law and Elasticity - Sari, Cindy Aida; Fitriyawany; Arusman (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2024)
The low literacy rate and lack of question discussion in schools were the driving forces behind this research. Those problems caused students to have difficulty in understanding the material on Hooke's Law and elasticity. The researchers developed the Minimum Competency Assessment (AKM) literacy instrument as a learning resource to address this issue. The study aims to find out: (1) how the AKM instrument for students' scientific literacy was made and (2) how excellent it works, how challenging the questions are, how valid it is, and how reliable it is for students' scientific literacy on Hooke's Law and Elasticity at the senior high school level. This R&D method reseach used the Tessmer model. The research instruments consisted of question grid sheets and question validation sheets. This study produced two question packages (A and B), each consisting of twelve questions. The researchers examined the AKM instrument for scientific literacy on 24 students from MAN 1 Model Banda Aceh. The feasibility results show that the AKM instrument has met the very feasible category. The validation results from material experts yielded a percentage of 92.44%, while language experts reported a percentage of 85.83%. The trial results show the discriminating ability of AKM Instrument packages A and B in the excellent and outstanding categories. Package A displays reliability results of 0.791, while package B of 0.805. The AKM instrument for scientific literacy based on Hooke's Law and elasticity can be used as a supporting learning resource in or outside of learning activities.